2010
DOI: 10.1111/j.1741-6612.2010.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Drought, drying and climate change: Emerging health issues for ageing Australians in rural areas

Abstract: Older Australians living in rural areas have long faced significant challenges in maintaining health. Their circumstances are shaped by the occupations, lifestyles, environments and remoteness which characterise the diversity of rural communities. Many rural regions face threats to future sustainability and greater proportions of the aged reside in these areas. The emerging changes in Australia's climate over the past decade may be considered indicative of future trends, and herald amplification of these famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…This result corresponded to findings from Australia and Taiwan because an increased impact of hot weather on rural mental health had been observed (34, 35). It is known that high vulnerability in rural communities can be predicted during variations or extremes in weather (36).…”
Section: Discussionsupporting
confidence: 90%
“…This result corresponded to findings from Australia and Taiwan because an increased impact of hot weather on rural mental health had been observed (34, 35). It is known that high vulnerability in rural communities can be predicted during variations or extremes in weather (36).…”
Section: Discussionsupporting
confidence: 90%
“…In rural areas for example, ageing Australians are particularly vulnerable due to isolation, environmental adversity, reduced access to health care and socioeconomic disadvantage. 24 The importance of behavioural adaptation during heat episodes Given the reasons discussed, it is important that older persons undertake adaptive behaviours during extreme heat to avoid the onset of heat-related pathology. The very old spend on average 80% of their time in their home, which studies have identified as being at the centre of their lives and a crucial aspect of their health.…”
Section: S18mentioning
confidence: 99%
“…This may be in part be explained by the fact, that until more recently, there has not been a body of evidence to demonstrate the types of practice that can have concurrent health and environmental benefits. Evidence that is now emerging highlight multiple co-benefits for the promotion of health and protection of the environment through initiatives centred on active and sustainable transport (Woodcock et al 2009;Rissel 2009); healthy and sustainable food systems (Larson 2008;Dixon et al 2009); and mental health promotion and climate change adaptation (Greenhill et al 2009;Horton et al 2010). In Victoria preliminary consultations by Olaris (2008) and Rowe and Thomas (2008) suggest that practitioners in Victoria's healthcare settings are beginning to respond to the emerging evidence and community interest by integrating concerns for the environment into practice.…”
Section: Introductionmentioning
confidence: 99%